2016
DOI: 10.1007/s00484-016-1197-9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-ecological factors and hand, foot and mouth disease in dry climate regions: a Bayesian spatial approach in Gansu, China

Abstract: The influence of socio-ecological factors on hand, foot and mouth disease (HFMD) were explored in this study using Bayesian spatial modeling and spatial patterns identified in dry regions of Gansu, China. Notified HFMD cases and socio-ecological data were obtained from the China Information System for Disease Control and Prevention, Gansu Yearbook and Gansu Meteorological Bureau. A Bayesian spatial conditional autoregressive model was used to quantify the effects of socio-ecological factors on the HFMD and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Hence, mapping the variation of spatial correlation residuals may explain other factors which may associated with geographical difference of JE incidence. The Bayesian CAR model has been widely used in examining the impact of social and climate variables on public health, including infectious disease [ 23 ], non-communicable disease [ 24 , 25 ] and injury [ 26 ]. We used the Bayesian CAR model with Poisson distribution to analyze the association of socio-environmental variables with JE incidence at the county level.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, mapping the variation of spatial correlation residuals may explain other factors which may associated with geographical difference of JE incidence. The Bayesian CAR model has been widely used in examining the impact of social and climate variables on public health, including infectious disease [ 23 ], non-communicable disease [ 24 , 25 ] and injury [ 26 ]. We used the Bayesian CAR model with Poisson distribution to analyze the association of socio-environmental variables with JE incidence at the county level.…”
Section: Methodsmentioning
confidence: 99%
“…These all increase the difficulty of characterizing the particular spatio-temporal transmission dynamics of a host-pathogen system. Previous studies mostly focus on the static spatio-temporal pattern of HFMD [15,16,[18][19][20][21], while its transmission mechanism over time and across space have not been discussed and is still unclear. Characterization of the particular spatio-temporal dynamics of a host-pathogen system can be used to illuminate the mechanisms most important in the dynamic system [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used GIS techniques to understand the spatial variations and trends in disease risk [ 1 , 6 9 ] or to explore the connections between spatial patterns in diseases and the corresponding risk factors on various geographic scales [ 2 5 , 10 12 ]. Those studies focused mainly on uncovering the spatial pattern of disease prevalence or incidence using spatial statistics and map visualization [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of them suggested that spatial patterns of diseases could be utilized as supporting evidence for further research on disease outbreak mechanisms. Further, many of those studies endeavored to explain the causes and risk factors of diseases with information derived from their spatial patterns [ 2 5 , 10 12 ]. Various analytic solutions and statistical methods, moreover, were utilized in exploring potential explanatory variables.…”
Section: Introductionmentioning
confidence: 99%